Pengaruh Sikap dan Norma Subyektif terhadap Keputusan Pembelian Barang secara Online melalui Aplikasi Shopee - Fahira Rizke Putri; Candra Wahyu Hidayat; Iva Nurdiana Nurfarida (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2018)
This study to determine the effect of attitudes and subjective norms on the decision to purchase goods online through the Shopee application (a study of students of the Faculty of Economics and Business, University of Kanjuruhan Malang). This type of research is quantitative research using an explanatory approach. The population in this study are students who have purchased goods online through the Shopee application at Kanjuruhan University Malang. The sampling technique is to use non probability sampling, which is a sampling technique that does not provide the same opportunity or opportunity for each element or member of the population to be selected as a sample. The sample in this study was 100 respondents. Based on existing sources there are two kinds of data sources, namely primary data and secondary data. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that partially the attitude variable and subjective norms have a significant effect on the decision to purchase goods online through the shopee application. While simultaneously the attitude and subjective norms have a significant effect on the decision to purchase goods online through the Shopee application. Key word:Purchasing Decisions, Attitudes, Subjective Norms